Tissue engineered constructs based on human adipose tissue derived stem cells and starch-based scaffolds for allogeneic approaches in tissue engineering and regenerative medicine - Santos, T. C. (2013)
Publicado em "Journa of Tissue Engineering and Regenerative Medicine", vol. 7, supp. 1 (2013)